The Windeby puzzle : history and story - Lowry, Lois. (New York, NY : Clarion Books, an imprint of HarperCollins Publishers, 2023)
Told in two voices, two outcasts in an Iron Age village befriend each other, as disabled, orphaned Varick helps Estrild achieve her dream of becoming the first female warrior. Inspired by the Windeby bog body.
Includes bibliographical references.
5-8.
English.
Keywords: Friendship -- Juvenile fiction; Iron age -- Juvenile fiction; Orphans -- Juvenile fiction; People with disabilities -- Juvenile fiction; Friendship -- Fiction; Iron age -- Fiction; Orphans -- Fiction; People with disabilities -- Fiction; Friendship -- Fiction; Iron Age -- Fiction; Orphans -- Fiction; People with disabilities -- Fiction; Historical fiction